How do postgraduate qualifications in medical education impact on health professionals?. (1st February 2016) - Sethi, Ahsan; Schofield, Susie; Ajjawi, Rola; McAleer, Sean
Abstract: Background and Purpose : The number of degree-awarding programmes in medical education is steadily increasing. Despite the popularity and extensive investment in these courses, there is little research into their impact. This study investigated the perceived impact of an internationally-renowned postgraduate programme in medical education on health professionals' development as educators. Methods : An online survey of the 2008–12 graduates from the Centre for Medical Education, University of Dundee was carried out. Their self-reported shifts in various educational competencies and scholarship activities were analysed using non-parametric statistics. Qualitative data were also collected and analysed to add depth to the quantitative findings. Results : Of the 504 graduates who received the online questionnaire 224 responded. Participants reported that a qualification in medical education had significantly ( p  < 0.001) improved their professional educational practices and engagement in scholarly activities. Masters graduates reported greater impact compared to Certificate graduates on all items, including ability to facilitate curriculum reforms, and in assessment and feedback practices. Masters graduates also reported more engagement in scholarship activities, with significantly greater contributions to journals. These qualifications equally benefited all participants regardless of age. International graduates reported greater impact of the qualification than their UK counterparts. Conclusion : A postgraduate medical education programme can significantly impact on the practices and behaviours of health professionals in education, improving self-efficacy and instilling an increased sense of belonging to the educational community.